Association between non-wire based computational angiography fractional flow reserve treatment threshold and major adverse cardiac events in patients with stable coronary artery disease. (14th October 2021) - Lam, L Y; Leung, C K L; Li, K Y; Wu, M Z; Ren, Q W; Li, H L; Yu, S S Y; Tse, Y K; Yu, A S Y; Wong, P F; Tse, H F; Feng, Y; et al.
Abstract: Introduction: Despite class IA guideline recommendations, the use of fractional flow reserve (FFR) in guiding percutaneous coronary intervention (PCI) in stable coronary artery disease (CAD) patients remains low due to limitations including the need of guidewire placement and hyperaemic stimulus. A novel non-invasive index, computational pressure-flow dynamics derived FFR (caFFR), was developed for measuring functional myocardial ischemia and overcoming the limitations of FFR. However, the clinical relevance of caFFR remains to be investigated. In the present study, we aim at evaluating the prognostic value of caFFR among stable CAD patients. Methods: We retrospectively included patients with stable CAD who underwent coronary angiography during 2014–2016 at our center. Based on the caFFR value, patients were considered to be ischemic (caFFR ≤0.8) and non-ischemic (caFFR >0.8). Further, we recombined the patients to form the adherence cohort, where patients were defined as adherent-to-caFFR if they were ischemic with PCI or non-ischemic without PCI, and nonadherent-to-caFFR if they were ischemic without PCI or non-ischemic with PCI. The primary endpoint was major adverse cardiac events (MACE), defined as a composite of all-cause mortality, non-fatal myocardial infarction, and any revascularization. Inverse probability of treatment weighting was used to account for treatment selection bias (PCI vs without PCI, or adherent vs non-adherent), and Cox proportional hazard model was used to evaluate the association with MACE. Results: A total of 1322 patients, 782 patients in the ischemic cohort and 540 patients in the non-ischemic cohort respectively, were included in our analysis. PCI was associated with a lower risk of MACE in the ischemic cohort (hazard ratio [HR] 0.52; 95% confidence interval [CI], 0.34–0.80; P=0.002), but was not associated with MACE in the non-ischemic cohort. In the adherence cohort, adherent-to-caFFR group (n=803) had a lower risk of MACE compared with nonadherent-to-caFFR group (n=566) (HR, 0.61; 95% CI, 0.44–0.85; P=0.003). Conclusion: Our study is the first to demonstrate the prognostic value of caFFR, a non-wire based assessment of myocardial ischemia, in patients with stable CAD undergoing PCI. These findings support the use of caFFR that bears the potential of a wider adoption compared with wire-based FFR through a reduction in procedure time, risk and costs. Funding Acknowledgement: Type of funding sources: None.